Fermentation, standardization and monitoring of physico-chemical changes of mango wine from carabao mangoes - Madrideo, Maria Imelda delos Santos; Francisco, Ma. Leonora dL. (2001., 2001)
With the desire to develop other products from "carabao" mangoes that did not pass the requirement for international market, the concept of developing wines from mangoes was studied. The formulations of fruit wines were selected. These formulation were prepared with the use of carabao mangoes. Resulting products were subjected to sensory evaluation to determine the most appropriate mango wine recipe. Results showed that the formulation used by Molinyawe (1989) was the most acceptable with "like lightly" rating. For the standardization process, three production runs were done using the same formulation of mango wine. The resulting mango wines were done subjected to sensory evaluation to test for significant differences in production trial. No significant difference was found among the wine from the three production runs. Another batch of the same wine formulation was done on a bench scale level. The must was analyzed for changes in pH, soluble solids, alcohol content, titratable acidity and tannin content during fermentation. Cost analysis of the mango was also done. Results of analysis showed that after five weeks o fermentation, mango wine had a final pH of 3.8, percent of titratable acidity of 0.43%, alcohol of 11.1%, soluble solids of 11.5° Brix, % and a negative result on tannin content. The values obtained were in the same trend as those of the literature values. In terms of cost analysis, 750-ml of mango wine costs P173.03. Price reduction is expected as the scale of production increased and when mangoes are in season.
Thesis (BSFT)--University of the Philippines Diliman
Keywords: Mangoes; Fruit wines